Switching-based hybrid FSO/RF transmission for cooperative communication system - Chau, Jing Sheng (2017)
Recent advancements in free-space optical(FSO) communications have allowed it to emerge as a viable alternative to today's wireless connections. FSO has been proposed to be a mean of signi cantly increasing bandwidth and reliability in wireless connections. The motivation is to understand the performance of Hybrid FSO/RF in dual-hop(DH) with decode and forward(DF) and cooperative DF relaying and direct link scenarios. In this thesis, we discuss the bene ts and reasons of using a hybrid FSO/RF system in DH and selection combining(SC) scenarios. We derive the mathematical expressions for outage probability of the hybrid FSO/RF system in three di erent scenarios, which are given as follows: 1. single link 2. DH with DF relaying, and 3. cooperative DF relaying with direct link considering SC. We also present the Monte-Carlo simulation results to validate the derived analytical outage probability expressions. Both numerical and simulation results are discussed to show the implications of using Hybrid FSO/RF system in di erent weather conditions. The simulation results show an improvement in the outage performance of hybrid FSO/RF system compared to the performance of FSO system. We also present the simulations of average bit error rate(BER) in both DH and SC scenarios and analyze the performance of hybrid FSO/RF considering di erent SNR values of RF and FSO links. From the simulation results, it can be inferred that the BER performance of the hybrid FSO/RF system is better than the performance of FSO system.